Electrode for power storage device and power storage device

By using the combination of oxide-based lithium-ion conductive solid electrolyte, active material and ionic liquid in the electrode of an all-solid lithium-ion secondary battery, the problems of low conductivity and insufficient safety of the electrode are solved, and the battery performance is achieved Improvement and security guarantee.

CN114270559BActive Publication Date: 2025-02-18NITERRA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080059071.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-08-22
Filing Date
2020-06-24
Publication Date
2025-02-18
Estimated Expiration
2040-06-24

AI Technical Summary

Technical Problem

In an all-solid lithium-ion secondary battery, when lithium-ion conductive solid electrolyte is added to the electrode, the low adhesion of oxide materials leads to a decrease in lithium-ion conductivity, while sulfide materials have shortcomings in terms of safety.

Method used

The electrodes are constructed with oxide-based lithium-ion conductive solid electrolyte, active material and ionic liquid, so as to avoid the use of sulfide-based materials that may produce toxic gases, and to improve lithium-ion conductivity through ionic liquids.

Benefits of technology

The lithium ion conductivity inside the electrode and at the interface between the electrode and other components is improved, the performance of the battery is enhanced, and safety is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114270559B_ABST
    Figure CN114270559B_ABST
Patent Text Reader

Abstract

The lithium ion conductivity of the electrode for a power storage device is improved in the electrode and at the interface between the electrode and other members. The electrode for a power storage device contains an oxide-based lithium ion conductive solid electrolyte, an active material and an ionic liquid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The technology disclosed in this specification relates to an electrode for a power storage device. Background Art

[0002] In recent years, with the popularization of electronic devices such as personal computers and mobile phones, the popularity of electric vehicles, and the expansion of the use of natural energy such as sunlight and wind power, the demand for high-performance batteries is increasing. Among them, the application of all-solid-state lithium-ion secondary batteries (hereinafter referred to as "all-solid-state batteries") in which all battery elements are composed of solids is expected. Compared with the previous type of lithium-ion secondary batteries using organic electrolytes dissolved in organic solvents with lithium salts, all-solid-state batteries have no risks of leakage or fire of organic electrolytes, so they are safe. In addition, the outer packaging can be simplified, so the energy density per unit mass or unit volume can be increased.

[0003] As the solid electrolyte constituting the solid electrolyte layer of the all-solid-state battery, for example, an oxide-based lithium ion conductive solid electrolyte or a sulfide-based lithium ion conductive solid electrolyte can be used. The oxide-based lithium ion conductive solid electrolyte is relatively hard in the powder state, so in the state of a compact (powder compact) obtained by press-forming the powder or in the state of a compact obtained by forming it into a sheet using a binder, the adhesion between particles is low and the lithium ion conductivity is low. The lithium ion conductivity can be improved by sintering and vapor deposition of the powder of the oxide-based lithium ion conductive solid electrolyte, but it is difficult to achieve large-scale batteries due to the warping and deformation associated with the heat treatment.

[0004] On the other hand, sulfide-based lithium ion conductive solid electrolytes are relatively soft in the powder state, so in the state of a compact obtained by press-molding the powder or a compact obtained by molding into a sheet using a binder, the adhesion between particles is high, and the lithium ion conductivity is high. However, sulfide-based lithium ion conductive solid electrolytes react with moisture in the atmosphere to generate hydrogen sulfide gas, so they are sometimes not preferred in terms of safety.

[0005] In addition, a technique is known in which an oxide-based lithium ion conductive solid electrolyte and a sulfide-based lithium ion conductive solid electrolyte are mixed to produce a lithium ion conductor, thereby achieving both improved safety and improved lithium ion conductivity (for example, see Patent Document 1).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: U.S. Patent Application Publication No. 2015 / 0171463 Summary of the invention

[0009] Problems to be solved by the invention

[0010] In an all-solid-state battery, for example, in order to improve the lithium ion conductivity of an electrode (positive electrode and / or negative electrode, the same below), it is considered to add a lithium ion conductive solid electrolyte to the electrode in addition to the active material. When an oxide-based lithium ion conductive solid electrolyte is used as a solid electrolyte added to the electrode, the adhesion between particles is low and the lithium ion conductivity is reduced in the state of a molded body obtained by press molding and in the state of a molded body obtained by molding into a sheet using a binder, as in the case of the above-mentioned solid electrolyte layer. On the other hand, when a sulfide-based lithium ion conductive solid electrolyte is used as a solid electrolyte added to the electrode, it is sometimes not preferred in terms of safety. In addition, when a mixture of an oxide-based lithium ion conductive solid electrolyte and a sulfide-based lithium ion conductive solid electrolyte as described above is used as a solid electrolyte added to the electrode, the content ratio of the sulfide-based lithium ion conductive solid electrolyte is reduced, but since a sulfide-based lithium ion conductive solid electrolyte is still included, there is room for improvement in terms of safety.

[0011] It should be noted that such a problem is not limited to electrodes for all-solid-state lithium-ion secondary batteries, but is a common problem for electrodes for power storage devices.

[0012] This specification discloses a technology that can solve the above-mentioned problems.

[0013] Means for solving problems

[0014] The technology disclosed in this specification can be implemented in the following manner, for example.

[0015] (1) The electrode for the storage device disclosed in this specification contains an oxide-based lithium ion conductive solid electrolyte, an active material and an ionic liquid. The electrode for the storage device does not contain a sulfide-based lithium ion conductive solid electrolyte that may produce toxic gas, but contains an oxide-based lithium ion conductive solid electrolyte that does not produce toxic gas, so the generation of toxic gas can be avoided. In addition, the oxide-based lithium ion conductive solid electrolyte is a material that is not easy to plastically deform, so when it is not fired, the contact between particles is insufficient and high lithium ion conductivity cannot be exerted. However, since the present electrode contains a non-volatile, flame-retardant and fluid ionic liquid that functions as a lithium ion conductive component, the presence of the ionic liquid can improve the lithium ion conductivity in the electrode and at the interface between the electrode and other components. Therefore, if the present electrode is used to form a storage device, the performance of the storage device can be improved.

[0016] (2) The following structure can be adopted in the electrode for the above-mentioned storage device: the volume content of the above-mentioned active material is 40 volume % or more and 85 volume % or less, the volume content of the above-mentioned oxide-based lithium ion conductive solid electrolyte is 5 volume % or more and 40 volume % or less, and the volume content of the above-mentioned ionic liquid is 3 volume % or more and 35 volume % or less. If such a structure is adopted, the lithium ion conductivity in the electrode and at the interface between the electrode and other components can be effectively improved. Therefore, if a storage device is constructed using an electrode with such a structure, the performance of the storage device can be effectively improved.

[0017] (3) The above-mentioned electrode for a power storage device may be configured as follows: the above-mentioned oxide-based lithium ion conductive solid electrolyte has a garnet-type crystal structure, and the garnet-type crystal structure contains at least Li, La, Zr and O. Compared with other oxide-based lithium ion conductive solid electrolytes, such an oxide-based lithium ion conductive solid electrolyte has a wider potential window, so if this configuration is adopted, the material selection range of the active material of the electrode can be expanded, and an electrode containing the most suitable active material substance can be configured.

[0018] (4) The power storage device disclosed in this specification may be configured as follows: the power storage device comprises a solid electrolyte layer, a positive electrode, a negative electrode, and a current collector, wherein at least one of the positive electrode and the negative electrode is an electrode for the power storage device. According to the power storage device, the performance of the power storage device can be improved by improving the lithium ion conductivity in the electrode and at the interface between the electrode and other components.

[0019] It should be noted that the technology disclosed in this specification can be implemented in various forms, for example, it can be implemented in the form of an electrode for a power storage device, a power storage device having the electrode for a power storage device, and methods for manufacturing the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] [ Figure 1 ] An explanatory diagram schematically showing a cross-sectional structure of an all-solid lithium ion secondary battery 102 in this embodiment

[0021] [ Figure 2 ] An explanatory diagram schematically showing a part of the structure of the positive electrode 114

[0022] [ Figure 3 ] An explanatory diagram schematically showing a part of the structure of the negative electrode 116

[0023] [ Figure 4 ] Illustration schematically showing the garnet crystal structure

[0024] [ Figure 5 ] An explanatory diagram showing the performance evaluation results of the positive electrode 114

[0025] [ Figure 6 ] An explanatory diagram showing the performance evaluation results of the positive electrode 114

[0026] [ Figure 7 ] An explanatory diagram showing the performance evaluation results of the negative electrode 116

[0027] [ Figure 8 ] An explanatory diagram showing the performance evaluation results of the negative electrode 116

[0028] [ Fig. 9 ] An explanatory diagram schematically showing the structure of the press jig 300 and the sample S used in the performance evaluation of the positive electrode 114

[0029] [ Fig.10 ] An explanatory diagram schematically showing the structure of the press jig 300 and the sample S used in the performance evaluation of the negative electrode 116 DETAILED DESCRIPTION

[0030] A. Implementation method:

[0031] A-1. Configuration of the all-solid-state battery 102:

[0032] (Overall composition)

[0033] Figure 1 1 is an explanatory diagram schematically showing the cross-sectional structure of an all-solid lithium ion secondary battery (hereinafter referred to as an "all-solid battery") 102 in this embodiment. Figure 1 The mutually orthogonal XYZ axes for defining directions are shown in FIG. In this specification, for convenience, the positive direction of the Z axis is referred to as the upward direction, and the negative direction of the Z axis is referred to as the downward direction.

[0034] The all-solid-state battery 102 includes a battery body 110, a positive electrode side current collector 154 disposed on one side (upper side) of the battery body 110, and a negative electrode side current collector 156 disposed on the other side (lower side) of the battery body 110. The positive electrode side current collector 154 and the negative electrode side current collector 156 are substantially flat plate-shaped members having conductivity, and are formed, for example, of a conductive metal material selected from stainless steel, Ni (nickel), Ti (titanium), Fe (iron), Cu (copper), Al (aluminum), and alloys thereof, a carbon material, and the like. In the following description, the positive electrode side current collector 154 and the negative electrode side current collector 156 are also collectively referred to as current collectors.

[0035] (Configuration of Battery Main Body 110)

[0036] The battery body 110 is a lithium-ion secondary battery body in which all battery elements are made of solid. It should be noted that, in this specification, the battery elements are all made of solid means that the skeleton of all battery elements is made of solid, and does not exclude the form of, for example, impregnated with liquid in the skeleton. The battery body 110 has a positive electrode 114, a negative electrode 116, and a solid electrolyte layer 112 arranged between the positive electrode 114 and the negative electrode 116. In the following description, the positive electrode 114 and the negative electrode 116 are also collectively referred to as electrodes. The all-solid-state battery 102 or the battery body 110 is equivalent to the storage device in the claims.

[0037] (Configuration of Solid Electrolyte Layer 112)

[0038] The solid electrolyte layer 112 is a member having a substantially flat plate shape and contains a lithium ion conductive solid electrolyte (for example, an LLZ-type lithium ion conductive solid electrolyte described later). The solid electrolyte layer 112 may also contain an ionic liquid having lithium ion conductivity. The solid electrolyte layer 112 may be a compact (powder compact) obtained by press-molding powder of a lithium ion conductive solid electrolyte, or may be a compact obtained by adding a binder to the powder of a lithium ion conductive solid electrolyte and molding it into a sheet shape.

[0039] (Configuration of Positive Electrode 114)

[0040] The positive electrode 114 is a substantially flat plate-shaped member. Figure 2 A portion of the positive electrode 114 is schematically shown ( Figure 1 The diagram is an illustration of the structure of the X1 part. Figure 2 As shown, the positive electrode 114 contains a positive electrode active material 214. For example, in order to increase the amount of lithium ions that can be inserted and released in the positive electrode 114 and improve the energy density, the positive electrode active material 214 is added. As the positive electrode active material 214, for example, S (sulfur), TiS2, LiCoO2 (hereinafter referred to as "LCO"), LiMn2O4, LiFePO4, Li(Co 1 / 3 Ni 1 / 3Mn 1 / 3 )O2 (hereinafter referred to as "NCM"), LiNi 0.8 Co 0.15 Al 0.05 O 2 (hereinafter referred to as “NCA”), etc. The positive electrode 114 may further contain a conductive auxiliary agent (for example, conductive carbon, Ni (nickel), Pt (platinum), Ag (silver)).

[0041] In addition, the positive electrode 114 contains an ionic liquid 224 having lithium ion conductivity. For example, the ionic liquid 224 is added to reduce the internal resistance of the positive electrode 114. The ionic liquid 224 having lithium ion conductivity is, for example, an ionic liquid in which a lithium salt is dissolved. It should be noted that the ionic liquid is composed only of cations and anions, is a liquid at room temperature, and is a non-volatile, flame-retardant substance. The specific materials of the ionic liquid 224 contained in the positive electrode 114 will be described later.

[0042] In addition, the positive electrode 114 contains an oxide-based lithium ion conductive solid electrolyte 204. For example, the oxide-based lithium ion conductive solid electrolyte 204 is added in order to suppress the reduction of the lithium ion conductivity of the positive electrode 114 and to suppress the corrosion of the positive electrode side current collector 154 by reducing the area of ​​the positive electrode side current collector 154 provided adjacent to the positive electrode 114 in contact with the ionic liquid 224. The specific materials of the oxide-based lithium ion conductive solid electrolyte 204 contained in the positive electrode 114 will be described later.

[0043] (Configuration of Negative Electrode 116)

[0044] The negative electrode 116 is a substantially flat plate-shaped member. Figure 3 A portion of the negative electrode 116 is schematically shown ( Figure 1 The diagram is an illustration of the structure of the X2 part. Figure 3 As shown, the negative electrode 116 contains a negative electrode active material 216. For example, the negative electrode active material 216 is added to increase the amount of lithium ions that can be inserted and released into the negative electrode 116 and to improve the energy density. As the negative electrode active material 216, for example, Li metal, Li-Al alloy, Li4Ti5O 12 (hereinafter referred to as "LTO"), carbon (graphite, natural graphite, artificial graphite, core-shell graphite coated with low-crystalline carbon on the surface), Si (silicon), SiO, etc. The negative electrode 116 may further contain a conductive auxiliary agent (e.g., conductive carbon, Ni, Pt, Ag).

[0045] In addition, the negative electrode 116 contains an ionic liquid 226 having lithium ion conductivity. For example, the ionic liquid 226 is added to reduce the internal resistance of the negative electrode 116. The ionic liquid 226 having lithium ion conductivity is, for example, an ionic liquid in which a lithium salt is dissolved. The specific material of the ionic liquid 226 contained in the negative electrode 116 will be described later.

[0046] In addition, the negative electrode 116 contains an oxide-based lithium ion conductive solid electrolyte 206. For example, the oxide-based lithium ion conductive solid electrolyte 206 is added to suppress the reduction of the lithium ion conductivity of the negative electrode 116 and to suppress the corrosion of the negative electrode side current collector 156 by reducing the area of ​​the negative electrode side current collector 156 provided adjacent to the negative electrode 116 in contact with the ionic liquid 226. The specific material of the oxide-based lithium ion conductive solid electrolyte 206 contained in the negative electrode 116 will be described later.

[0047] A-2. Detailed structure of the positive electrode 114 and the negative electrode 116:

[0048] Next, the structure of the electrodes (positive electrode 114 and negative electrode 116) constituting the battery body 110 is described in further detail. As described above, the positive electrode 114 contains an oxide-based lithium ion conductive solid electrolyte 204 in addition to the positive electrode active material 214, and the negative electrode 116 contains an oxide-based lithium ion conductive solid electrolyte 206 in addition to the negative electrode active material 216. As the oxide-based lithium ion conductive solid electrolyte 204, 206, for example, a solid electrolyte having a garnet-type crystal structure can be used, and the garnet-type crystal structure contains at least Li (lithium), La (lanthanum), Zr (zirconium) and O (oxygen). More specifically, for example, Li7La3Zr2O 12 The present invention relates to a lithium-ion conductive solid electrolyte (hereinafter referred to as "LLZ"), or a substance obtained by replacing LLZ with at least one of Mg (magnesium) and A (A is at least one element selected from the group consisting of Ca (calcium), Sr (strontium) and Ba (barium)) (for example, a substance obtained by replacing LLZ with Mg and Sr (hereinafter referred to as "LLZ-MgSr")). Hereinafter, these lithium-ion conductive solid electrolytes are referred to as "LLZ-type lithium-ion conductive solid electrolytes (or LLZ-type ion conductive powders)".

[0049] It should be noted that the "garnet-type crystal structure" refers to the general formula C3A2B3O 12 Represents the crystal structure. Figure 4 is an explanatory diagram schematically showing the garnet type crystal structure. Figure 4 As shown, in the garnet-type crystal structure, the C site Sc is coordinated with the oxygen atom Oa in a 12-hedron, the A site Sa is coordinated with the oxygen atom Oa in an octahedron, and the B site Sb is coordinated with the oxygen atom Oa in a tetrahedron. It should be noted that in the lithium ion conductive powder (lithium ion conductive solid electrolyte) having a garnet-type crystal structure, in the usual garnet-type crystal structure, lithium can exist in the site that is coordinated with the oxygen atom Oa in an octahedron and forms a void V. The void V is, for example, Figure 4The lithium in the gap V is coordinated with the oxygen atom Oa constituting an octahedron, and the octahedron includes a tetrahedron face Fb1 forming the B site Sb1 and a tetrahedron face Fb2 forming the B site Sb2. For example, in the case of Li7La3Zr2O 12 In the lithium ion conductive powder (lithium ion conductive solid electrolyte) having a garnet-type crystal structure, lanthanum can occupy the C site Sc, zirconium can occupy the A site Sa, and lithium can occupy the B site Sb and the void V.

[0050] In addition, the lithium ion conductive solid electrolyte (lithium ion conductive powder) has a garnet-type crystal structure containing at least Li, La, Zr and O, which can be confirmed by X-ray diffraction (XRD) analysis. Specifically, the lithium ion conductive solid electrolyte is analyzed by using an X-ray diffraction device to obtain an X-ray diffraction pattern. The obtained X-ray diffraction pattern is compared with the ICDD (International Center for Diffraction Data) card (01-080-4947) corresponding to LLZ (Li7La3Zr2O 12 ) are compared, and if the diffraction angles and diffraction intensity ratios of the diffraction peaks of the two are substantially consistent, it can be determined that the lithium ion conductive solid electrolyte has a garnet-type crystal structure containing at least Li, La, Zr and O. For example, since the diffraction angles and diffraction intensity ratios of the diffraction peaks of the X-ray diffraction pattern obtained from the lithium ion conductive powder and the ICDD card corresponding to LLZ are substantially consistent, each lithium ion conductive powder described in "A-7. Preferred embodiment of LLZ-based ion conductive powder" described later is determined to have a garnet-type crystal structure containing at least Li, La, Zr and O.

[0051] In addition, as the oxide-based lithium ion conductive solid electrolytes 204 and 206 , solid electrolytes other than the LLZ-based lithium ion conductive solid electrolytes (for example, the following solid electrolytes) may be used.

[0052] (1) A solid electrolyte having a NASICON crystal structure containing at least Li, M (M is at least one of Ti, Zr, and Ge (germanium)), P (phosphorus), and O (e.g., (Li, Ti, Al)(PO4)3, LiZr2(PO4)3, (Li, Ge, Al)(PO4)3)

[0053] (2) A solid electrolyte having a perovskite crystal structure containing at least Li, Ti, La, and O (e.g., (La, Li)TiO3)

[0054] (3) A solid electrolyte having an antiperovskite crystal structure containing at least Li, Cl and O (e.g., Li2(OH)Cl)

[0055] (4) Complex hydride

[0056] It should be noted that the average particle size of the oxide-based lithium ion conductive solid electrolytes 204 and 206 contained in the electrodes (positive electrode 114 and negative electrode 116 ) is preferably 0.1 μm or more and 10 μm or less.

[0057] In addition, as described above, the positive electrode 114 contains an ionic liquid 224 in which a lithium salt is dissolved, and the negative electrode 116 contains an ionic liquid 226 in which a lithium salt is dissolved. As the above-mentioned lithium salt, for example, lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium trifluoromethanesulfonate (CF3SO3Li), lithium bis(trifluoromethanesulfonyl)imide (LiN(SO2CF3)2) (hereinafter referred to as "Li-TFSI"), lithium bis(fluorosulfonyl)imide (LiN(SO2F)2) (hereinafter referred to as "Li-FSI"), lithium bis(pentafluoroethanesulfonyl)imide (LiN(SO2C2F5)2), etc. can be used.

[0058] In addition, as the above-mentioned ionic liquid, an ionic liquid having the following substances as cations can be used:

[0059] Ammoniums such as butyltrimethylammonium and trimethylpropylammonium;

[0060] 1-Ethyl-3-methylimidazole , 1-butyl-3-methylimidazole Imidazole kind,

[0061] 1-Butyl-1-methylpiperidine , 1-methyl-1-propylpiperidine Isopiperidine kind,

[0062] 1-Butyl-4-methylpyridine , 1-ethylpyridine Isopyridine kind,

[0063] 1-Butyl-1-methylpyrrolidine , 1-methyl-1-propylpyrrolidine Isopyrrolidine kind,

[0064] Sulfoniums such as trimethylsulfonium and triethylsulfonium,

[0065] kind,

[0066] Morpholine Class, etc.

[0067] In addition, as the above-mentioned ionic liquid, an ionic liquid having the following substances as anions can be used:

[0068] Cl - Br - Halides, etc.

[0069] BF4 - Borides, etc.

[0070] (NC)2N - ,

[0071] (CF3SO2)2N - 、(FSO2)2N - Amines,

[0072] CH3SO4 - ,

[0073] CF3SO3 - Sulfate, sulfonate, etc.

[0074] PF6 - Phosphoric acids, etc.

[0075] More specifically, as the above-mentioned ionic liquid, butyltrimethylammonium bis(trifluoromethanesulfonyl)imide, trimethylpropylammonium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazole, Bis(fluorosulfonyl)imide (hereinafter referred to as "EMI-FSI"), 1-ethyl-3-methylimidazole Tetrafluoroborate, 1-methyl-1-propylpyrrolidine Bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazole Bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyrrolidine Bis(fluorosulfonyl)imide (hereinafter referred to as "P13-FSI"), 1-methyl-1-propylpiperidin Bis(fluorosulfonyl)imide (hereinafter referred to as "PP13-FSI") and the like.

[0076] It should be noted that the electrodes (positive electrode 114 and negative electrode 116) of the present embodiment are not sintered bodies formed by high-temperature firing. Therefore, the electrodes of the present embodiment contain hydrocarbons. More specifically, the ionic liquid constituting the electrodes of the present embodiment contains hydrocarbons. It should be noted that the fact that the electrode (ionic liquid) contains hydrocarbons can be determined by a combination of one or more methods such as NMR (nuclear magnetic resonance), Raman spectroscopy, LC-MS (liquid chromatography mass spectrometry), GC-MS (gas chromatography mass spectrometry), FT-IR (Fourier transform infrared spectroscopy), etc.

[0077] As described above, the electrodes (positive electrode 114 and negative electrode 116) of the present embodiment contain not only the oxide-based lithium ion conductive solid electrolyte 204, 206 and the active material (positive electrode active material 214, negative electrode active material 216), but also the ionic liquid 224, 226 having lithium ion conductivity, and have high lithium ion conductivity in the state of the compact (compressed powder) obtained by pressure molding. Therefore, if the electrodes of the present embodiment are used, the performance of the battery body 110 can be improved. It should be noted that the reason why the electrodes of the present embodiment have such high lithium ion conductivity is not necessarily clear, but it is speculated as follows.

[0078] Generally, oxide-based lithium ion conductive solid electrolytes are harder than lithium ion conductive solid electrolytes other than oxides (for example, sulfide-based lithium ion conductive solid electrolytes). Therefore, in the state of a compact (compressed powder) obtained by press-molding the powder of the oxide-based lithium ion conductive solid electrolyte, the contact between the particles becomes point contact, the resistance between the particles becomes high, and the lithium ion conductivity becomes relatively low. In addition, by firing the powder of the oxide-based lithium ion conductive solid electrolyte at a high temperature, the lithium ion conductivity can be improved, but since warping and deformation occur with high-temperature firing, it is difficult to achieve a large-scale battery. In addition, due to the reaction with the electrode active material and the like accompanying the high-temperature firing, a high-resistance layer is generated, and the lithium ion conductivity may be reduced. However, the electrodes (positive electrode 114 and negative electrode 116) of the present embodiment contain ionic liquids 224 and 226 having lithium ion conductivity in addition to the oxide-based lithium ion conductive solid electrolytes 204 and 206. As Figure 2 and Figure 3 As shown, the ionic liquids 224 and 226 are distributed around the particles of the oxide-based lithium ion conductive solid electrolytes 204 and 206. Therefore, it is considered that in the state of the compact obtained by pressure molding, the ionic liquids 224 and 226 that function as lithium ion conductive paths are interspersed in the grain boundaries of the oxide-based lithium ion conductive solid electrolytes 204 and 206 in the entire compact, and the lithium ion conductivity at the grain boundaries is improved, resulting in the improvement of the lithium ion conductivity in the electrode and at the interface between the electrode and other members (for example, the solid electrolyte layer 112).

[0079] It should be noted that the electrodes (positive electrode 114 and negative electrode 116) of the present embodiment contain not only the oxide-based lithium ion conductive solid electrolyte 204, 206, active materials (positive electrode active material 214, negative electrode active material 216) and ionic liquids 224, 226, but also a binder, and may be formed in a sheet shape. As the binder, for example, polyvinylidene fluoride (PVDF), a copolymer of polyvinylidene fluoride (PVDF) and hexafluoropropylene (HFP) (hereinafter referred to as "PVDF-HFP"), polytetrafluoroethylene (PTFE), polyimide, polyamide, silicone resin (polysiloxane), styrene butadiene rubber (SBR), acrylic resin (PMMA), polyethylene oxide (PEO), etc. can be used. If such a structure is adopted, it is possible to improve the lithium ion conductivity of the electrode while improving the formability and handling properties of the electrode.

[0080] In addition, in the electrodes (positive electrode 114 and negative electrode 116) of the present embodiment, the volume content of the active material (positive electrode active material 214, negative electrode active material 216) is preferably 40% by volume or more and 85% by volume or less. When the volume content of the active material in the electrode is too low, the capacity of the battery cannot be fully ensured. On the other hand, when the volume content of the active material in the electrode is too high, the internal resistance of the electrode cannot be effectively reduced. The volume content of the active material in the electrode is further preferably 40% by volume or more and 70% by volume or less.

[0081] In addition, in the electrodes (positive electrode 114 and negative electrode 116), the volume content of the oxide-based lithium ion conductive solid electrolyte 204, 206 is preferably 5 volume % or more and 40 volume % or less. When the volume content of the oxide-based lithium ion conductive solid electrolyte 204, 206 in the electrode is too low, the reduction in the lithium ion conductivity of the electrode cannot be suppressed, and the corrosion of the current collector cannot be effectively suppressed. On the other hand, when the volume content of the oxide-based lithium ion conductive solid electrolyte 204, 206 in the electrode is too high, the internal resistance of the electrode cannot be effectively reduced. The volume content of the oxide-based lithium ion conductive solid electrolyte 204, 206 in the electrode is more preferably 10 volume % or more and 40 volume % or less, and more preferably 20 volume % or more and 40 volume % or less.

[0082] In addition, in the electrodes (positive electrode 114 and negative electrode 116), the volume content of the ionic liquids 224 and 226 is preferably 3% by volume or more and 35% by volume or less. When the volume content of the ionic liquids 224 and 226 in the electrodes is too low, the internal resistance of the electrodes cannot be effectively reduced. On the other hand, when the volume content of the ionic liquids 224 and 226 in the electrodes is too high, the ionic liquid may leak out. The volume content of the ionic liquids 224 and 226 in the electrodes is more preferably 10% by volume or more and 25% by volume or less.

[0083] For the electrodes (positive electrode 114 and negative electrode 116), if the volume content of the active materials (positive electrode active material 214, negative electrode active material 216) is set to be greater than 40 volume % and less than 85 volume %, the volume content of the oxide-based lithium ion conductive solid electrolytes 204, 206 is set to be greater than 5 volume % and less than 40 volume %, and the volume content of the ionic liquids 224, 226 is set to be greater than 3 volume % and less than 35 volume %, it is possible to effectively improve the lithium ion conductivity within the electrode and at the interface between the electrode and other components (for example, the solid electrolyte layer 112) while suppressing the corrosion of the collector and the occurrence of ionic liquid seepage, and it is possible to effectively improve the performance of the battery body 110 using the electrode.

[0084] A-3. Method for manufacturing all-solid-state battery 102:

[0085] Next, an example of a method for manufacturing the all-solid-state battery 102 of the present embodiment is described. First, a solid electrolyte layer 112 is prepared. For example, a powder of an oxide-based lithium ion conductive solid electrolyte is mixed with an ionic liquid, and the mixture is press-formed under a predetermined pressure or formed into a sheet by adding a binder, thereby preparing the solid electrolyte layer 112.

[0086] In addition, the positive electrode 114 and the negative electrode 116 are separately prepared. Specifically, the powder of the oxide-based lithium ion conductive solid electrolyte 204 is mixed with the ionic liquid 224, and the powder of the positive electrode active material 214 (a mixture of the powder of the positive electrode active material 214 and the conductive auxiliary agent when a conductive auxiliary agent is used) is added to the mixture and further mixed. The mixture is press-formed at a predetermined pressure or formed into a sheet by adding a binder, thereby preparing the positive electrode 114. Similarly, the powder of the oxide-based lithium ion conductive solid electrolyte 206 is mixed with the ionic liquid 226, and the powder of the negative electrode active material 216 (a mixture of the powder of the negative electrode active material 216 and the conductive auxiliary agent when a conductive auxiliary agent is used) is added to the mixture and further mixed. The mixture is press-formed at a predetermined pressure or formed into a sheet by adding a binder, thereby preparing the negative electrode 116.

[0087] Next, the positive electrode collector 154, the positive electrode 114, the solid electrolyte layer 112, the negative electrode 116, and the negative electrode collector 156 are stacked in order and pressurized to be integrated. Through the above steps, the all-solid battery 102 having the above structure is manufactured.

[0088] A-4. Effects of this embodiment:

[0089] As described above, the electrodes (positive electrode 114 and negative electrode 116) used in the battery body 110 of the present embodiment contain the oxide-based lithium ion conductive solid electrolytes 204 and 206, active materials (positive electrode active material 214 and negative electrode active material 216), and ionic liquids 224 and 226. As described above, the electrodes (positive electrode 114 and negative electrode 116) of the present embodiment do not contain the sulfide-based lithium ion conductive solid electrolyte that may generate poisonous gas, but contain the oxide-based lithium ion conductive solid electrolytes 204 and 206 that are unlikely to generate poisonous gas, thereby preventing the generation of poisonous gas. In addition, the oxide-based lithium ion conductive solid electrolytes 204 and 206 are materials that are not easily deformed by plastic deformation, so when not fired, the contact between the particles is insufficient and high lithium ion conductivity cannot be exerted. However, since the electrodes (positive electrode 114 and negative electrode 116) of this embodiment contain non-volatile, flame-retardant and fluid ionic liquids 224 and 226 that function as lithium ion conductive components, the lithium ion conductivity in the electrodes and at the interface between the electrodes and other components (for example, solid electrolyte layer 112) can be improved by the presence of the ionic liquids 224 and 226. Therefore, if the battery body 110 is constructed using the electrodes of this embodiment, the performance of the battery body 110 can be improved.

[0090] It should be noted that, since the electrodes (positive electrode 114 and negative electrode 116) of the present embodiment contain the oxide-based lithium ion conductive solid electrolyte 204, 206, the area of ​​the ionic liquid 224, 226 contacting the current collector (positive electrode side current collector 154 and negative electrode side current collector 156) disposed adjacent to the electrodes can be reduced, and corrosion of the current collector can be suppressed. As described above, when the concentration of the lithium salt contained in the ionic liquid 224, 226 is high (specifically, when it is 0.4 mol / L or more), corrosion of the current collector is likely to occur, so the corrosion suppression effect of the current collector brought about by the inclusion of the oxide-based lithium ion conductive solid electrolyte 204, 206 becomes more useful.

[0091] In addition, in the electrodes (positive electrode 114 and negative electrode 116) of the present embodiment, the volume content of the active material (positive electrode active material 214, negative electrode active material 216) is preferably 40 volume % or more and 85 volume % or less, the volume content of the oxide-based lithium ion conductive solid electrolyte 204, 206 is preferably 5 volume % or more and 40 volume % or less, and the volume content of the ionic liquid 224, 226 is preferably 3 volume % or more and 35 volume % or less. If such a structure is adopted, the lithium ion conductivity in the electrode and at the interface between the electrode and other members (for example, the solid electrolyte layer 112) can be effectively improved. Therefore, if the battery body 110 is constructed using an electrode having such a structure, the performance of the battery body 110 can be effectively improved.

[0092] In addition, the oxide-based lithium ion conductive solid electrolytes 204 and 206 contained in the electrodes (positive electrode 114 and negative electrode 116) of the present embodiment are preferably solid electrolytes having a garnet-type crystal structure (LLZ-based lithium ion conductive solid electrolytes) containing at least Li, La, Zr, and O. Compared with other oxide-based lithium ion conductive solid electrolytes, the LLZ-based lithium ion conductive solid electrolyte has a wider potential window, so that the material selection range of the active material of the electrode (positive electrode active material 214, negative electrode active material 216) can be expanded, and an electrode containing the optimal active material substance can be formed. For example, as the positive electrode active material, LCO, LiMn2O4, LiFePO4, NCM, NCA, etc. can be listed, and as the negative electrode active material, Li metal, Li-Al alloy, LTO, carbon (graphite, natural graphite, artificial graphite, core-shell graphite coated with low crystalline carbon on the surface), Si (silicon), SiO, etc. can be listed.

[0093] A-5. Method for determining the composition of the electrode (volume content of each component):

[0094] The composition of the electrodes (positive electrode 114, negative electrode 116) constituting the battery body 110, i.e., the volume content (volume %) of the active materials (positive electrode active material 214, negative electrode active material 216), the oxide-based lithium ion conductive solid electrolytes 204, 206 and the ionic liquids 224, 226 is determined as follows.

[0095] The electrode mixture material to be used is dissolved in a solvent (e.g., chloroform) and separated into soluble matter (binder, ionic liquid) and precipitate (active material, oxide-based lithium ion conductive solid electrolyte, conductive aid). For the soluble matter, the material components (ionic liquid, binder) are qualitatively analyzed by LC-MS measurement (liquid chromatography mass spectrometry) to determine the components of the binder and the ionic liquid. In addition, by making a calibration curve for each material component, the content of each component in the entire soluble matter is calculated from the results of each material component.

[0096] The weight of the precipitate is measured as a whole. In addition, the chemical composition is analyzed by performing XRD measurement (X-ray analysis) on the precipitate to determine the material composition of the active material and the oxide-based lithium ion conductive solid electrolyte. In addition, the ratio of the material composition is measured by performing XRF measurement (fluorescent X-ray analysis) on the precipitate. Thus, the ratio of the active material, the oxide-based lithium ion conductive solid electrolyte and the conductive auxiliary agent is determined. The content of the active material and the oxide-based lithium ion conductive solid electrolyte is calculated from the weight of the whole precipitate and the ratio of the active material, the oxide-based lithium ion conductive solid electrolyte and the conductive auxiliary agent.

[0097] The volume content of each component is determined from the content of each component (binder, ionic liquid, active material, oxide-based lithium ion conductive solid electrolyte) calculated above.

[0098] It should be noted that the ratio of the active material to the oxide-based lithium ion conductive solid electrolyte can also be obtained by the following method. For the electrode as the object, in order to obtain a state in which each substance is fixed, it is frozen using liquid nitrogen or the like, and a cross section is obtained by the CP method (cross section polishing machine method). The cross section is used as the object, and element mapping using EDS (energy dispersive X-ray analysis) is performed, thereby being able to obtain the volume ratio of the active material to the oxide-based lithium ion conductive solid electrolyte.

[0099] A-6. Performance evaluation:

[0100] The performance of the electrodes (positive electrode 114 and negative electrode 116) used in the battery body 110 was evaluated. Figure 5 and Figure 6 1 is an explanatory diagram showing the performance evaluation results of the positive electrode 114. Figure 7 and Figure 8 1 is an explanatory diagram showing the performance evaluation results of the negative electrode 116. Fig. 9 1 is an explanatory diagram schematically showing the configuration of a press jig 300 and a sample S used in the performance evaluation of a positive electrode 114. Fig.10 It is an explanatory diagram schematically showing the configuration of a press jig 300 and a sample S used in the performance evaluation of the negative electrode 116 .

[0101] like Figure 5 and Figure 6 As shown in FIG. 1 , 12 samples (S1 to S12) were used in the performance evaluation of the positive electrode 114. Figure 7 and Figure 8 As shown, 13 samples (S21 to S33) were used in the performance evaluation of the negative electrode 116. The compositions (materials and volume contents of each component) of the samples were different from each other for the positive electrode 114 and the negative electrode 116.

[0102] like Figure 5 and Figure 6 As shown, for the positive electrode 114, samples S1 to S10 are sheet-like formed bodies containing a positive electrode active material 214, an oxide-based lithium ion conductive solid electrolyte 204, an ionic liquid 224, a conductive auxiliary agent, and a binder. In addition, sample S11 is a powder compact containing a positive electrode active material 214, an oxide-based lithium ion conductive solid electrolyte 204, an ionic liquid 224, and a conductive auxiliary agent but not containing a binder. On the other hand, sample S12 is a sheet-like formed body containing a positive electrode active material 214, an oxide-based lithium ion conductive solid electrolyte 204, a conductive auxiliary agent, and a binder, but unlike the other samples, does not contain an ionic liquid 224.

[0103] It should be noted that as the positive electrode active material 214, the above-mentioned NCA (LiNi 0.8 Co 0.15 Al 0.05 O2), the above LCO (LiCoO2) was used in sample S10, and the above NCM (Li(Co 1 / 3 Ni 1 / 3 Mn 1 / 3 )O2). In addition, as the oxide-based lithium ion conductive solid electrolyte 204, the above-mentioned LLZ-Mg and Sr are used in all samples. In addition, as the ionic liquid 224, the ionic liquid EMI-FSI (hereinafter referred to as "Li-FSI (EMI-FSI)") in which the above-mentioned lithium salt Li-FSI is dissolved is used in samples S1 to S9 (lithium salt concentration: 1.0M (= mol / L)), and the ionic liquid EMI-FSI (hereinafter referred to as "Li-TFSI (EMI-FSI)") in which the above-mentioned lithium salt Li-TFSI is dissolved is used in samples S10 and S11 (lithium salt concentration: 0.8M). In addition, as a conductive additive, acetylene black (AB) is used in samples S1 to S6, S11, and S12, and vapor grown carbon fiber (VGCF) is used in samples S7 to S10. In addition, as an adhesive, the above-mentioned PVDF-HFP is used in the samples containing the adhesive (S1 to S10, S12).

[0104] In addition, if Figure 7 and Figure 8 As shown, for the negative electrode 116, samples S21 to S30, S32 are sheet-like formed bodies containing a negative electrode active material 216, an oxide-based lithium ion conductive solid electrolyte 206, an ionic liquid 226, and a binder. It should be noted that samples S29, S30, and S32 also contain a conductive additive (VGCF). In addition, sample S31 is a powder compact containing a negative electrode active material 216, an oxide-based lithium ion conductive solid electrolyte 206, and an ionic liquid 226 but not containing a binder. On the other hand, sample S33 is a sheet-like formed body containing a negative electrode active material 216, an oxide-based lithium ion conductive solid electrolyte 206, and a binder, but unlike the other samples, does not contain an ionic liquid 226.

[0105] It should be noted that, as the negative electrode active material 216, artificial graphite (MCMB) was used in samples S21 to S27, S31 to S33, and natural graphite was used in samples S28 to S30. In addition, as the oxide-based lithium ion conductive solid electrolyte 206, the above-mentioned LLZ-Mg and Sr were used in all samples. In addition, as the ionic liquid 226, 1.0M Li-FSI (EMI-FSI) was used in all samples (S21 to S32) containing the ionic liquid 226. In addition, as the binder, the above-mentioned PVDF-HFP was used in all samples (S21 to S30, S32, S33) containing the binder.

[0106] Each sample was prepared according to the following steps, and the discharge capacity of each sample was measured. First, LLZ-MgSr powder as an oxide-based lithium ion conductive solid electrolyte was prepared in the following manner. That is, according to the composition: Li 6.95 Mg 0.15 La 2.75 Sr 0.25 Zr 2.0 O 12 (LLZ-MgSr) Li2CO3, MgO, La(OH)3, SrCO3, and ZrO2 are weighed. At this time, Li2CO3 is further added in an excess of about 15 mol% in terms of element conversion in consideration of the volatilization of Li during firing. The raw material is put into a nylon pot together with zirconium oxide balls, and pulverized and mixed in an organic solvent using a ball mill for 15 hours. After pulverization and mixing, the slurry is dried and pre-fired on a MgO plate at 1100°C for 10 hours. A binder is added to the pre-fired powder, and pulverized and mixed in an organic solvent using a ball mill for 15 hours. After pulverization and mixing, the slurry is dried, put into a metal mold with a diameter of 12 mm, and pressed to a thickness of about 1.5 mm, and then a cold isostatic press (CIP) is used to apply 1.5 t / cm 2The molded body was covered with a pre-calcined powder of the same composition as the molded body and fired at 1100°C for 4 hours in a reducing atmosphere to obtain a sintered body. The sintered body was crushed in a glove box in an argon atmosphere to obtain a powder of LLZ-MgSr. The particle size of the obtained LLZ-MgSr was about 0.3μm to 0.8μm.

[0107] To the powder of the oxide-based lithium ion conductive solid electrolyte (LLZ-MgSr) obtained in this manner, the ionic liquid specified for each sample was added and mixed in a mortar to obtain a mixed material of the solid electrolyte and the ionic liquid. In addition, for the positive electrode 114, the positive electrode active material 214 and the conductive auxiliary agent specified for each sample were added and mixed in a mortar, and the mixed material was added to the mixed material of the solid electrolyte and the ionic liquid (wherein, for sample S12, it was a solid electrolyte) and mixed, thereby obtaining an electrode composite powder. In addition, for the negative electrode 116, the negative electrode active material 216 specified for each sample was added to the mixed material of the solid electrolyte and the ionic liquid (wherein, for sample S33, it was a solid electrolyte) and mixed, thereby obtaining an electrode composite powder.

[0108] In addition, for samples containing adhesives, 10 wt% PVDF-DMC (dimethyl carbonate) solution was added to the above-mentioned electrode composite powder in small amounts multiple times, and mixed in an agate mortar, and DMC solvent was further added multiple times in small amounts each time to adjust the viscosity, thereby obtaining an electrode composite slurry. The electrode composite slurry was applied to a metal foil uniformly attached to glass using DMC and a roller using an applicator, and dried under reduced pressure at 80°C for 10 hours, thereby obtaining an electrode composite sheet.

[0109] Then, if Fig. 9 and Fig.10As shown, a Macor tube is set on the short axis of the pressurizing fixture 300, and 150 mg of a mixed material (material for the solid electrolyte layer) of an oxide-based lithium ion conductive solid electrolyte (LLZ-MgSr) and an ionic liquid (1.0M Li-FSI (EMI-FSI)) prepared separately is weighed and put in. Then, the long axis is set on the Macor tube and pressurized at 100 MPa. After pressurization, the short axis is pulled out, and the material of the electrode (positive electrode 114 or negative electrode 116), that is, an electrode composite sheet (or electrode composite powder) punched out with a diameter of 10 mm is put in, and the short axis is set on the Macor tube, and pressurized at 500 MPa. Then, the pressurizing fixture is reversed, the long axis is pulled out, and the material of the counter electrode, that is, In-Li foil punched out with a diameter of 10 mm, is put in, and then Cu foil punched out with a diameter of 10 mm is put in, and then the long axis is set on the Macor tube and pressurized at 80 MPa. Then, the fixing jig (shaft collar) was installed and fastened with bolts at a force of 8N.

[0110] In this state, at a current density of 50 μA / cm 2 The battery was discharged under the conditions of 2.0V to 3.9V (when NCM was used as the positive electrode active material 214 in the sample of the positive electrode 114), 2.0V to 3.7V (when NCA or LCO was used as the positive electrode active material 214 in the sample of the positive electrode 114), and -0.6V to 1.0V (the sample of the negative electrode 116), and the initial discharge capacity was measured. For the positive electrode 114, when the discharge capacity was less than 50 μAh, it was judged as "×" (unqualified), when the discharge capacity was 50 μAh or more and less than 400 μAh, it was judged as "0" (qualified), and when the discharge capacity was 400 μAh or more, it was judged as "◎" (excellent). For the negative electrode 116, when the discharge capacity is less than 100 μAh, it is judged as "×" (unqualified), when the discharge capacity is greater than 100 μAh and less than 400 μAh, it is judged as "○" (qualified), and when the discharge capacity is greater than 400 μAh, it is judged as "◎" (excellent).

[0111] like Figure 5 and Figure 6 As shown, for the positive electrode 114, in the sample S12 not containing the ionic liquid 224, the discharge capacity is less than 50 μAh, and it is judged as unqualified (×). It is believed that since the sample S12 does not contain the ionic liquid 224, the contact between the particles of the oxide-based lithium ion conductive solid electrolyte 204 becomes point contact, and the resistance between the particles becomes high. As a result, the lithium ion conductivity in the electrode and at the interface between the electrode and other components is reduced, and the capacity of the battery is reduced.

[0112] In contrast, in samples S1 to S11 (except for sample S6) containing the ionic liquid 224, the discharge capacity was 50 μAh or more, and thus they were judged as acceptable (○) or excellent (◎). It is believed that since these samples contain the ionic liquid 224, the ionic liquid 224, which functions as a lithium ion conduction path, is interspersed between particles of the oxide-based lithium ion conductive solid electrolyte 204, and the lithium ion conductivity at the grain boundary is improved. As a result, the lithium ion conductivity in the electrode and at the interface between the electrode and other components is improved, and the capacity of the battery is increased. From this result, it can be said that when the positive electrode 114 contains the ionic liquid 224 in addition to the oxide-based lithium ion conductive solid electrolyte 204 and the positive electrode active material 214, the lithium ion conductivity in the electrode and at the interface between the electrode and other components can be improved.

[0113] It should be noted that in samples S7 to S11, the discharge capacity is above 400 μAh, so it is judged to be excellent (◎). In these samples, the volume content of the positive electrode active material 214 is above 40 volume % and below 85 volume %, the volume content of the oxide-based lithium ion conductive solid electrolyte 204 is above 5 volume % and below 40 volume %, and the volume content of the ionic liquid 224 is above 3 volume % and below 35 volume %. On the other hand, sample S6 has ionic liquid seepage during molding, so it is judged to be unmeasurable (-). From these results, it can be said that if the electrode meets the above-mentioned conditions on the volume content, it can effectively improve the lithium ion conductivity in the electrode and at the interface between the electrode and other components while suppressing the occurrence of ionic liquid seepage.

[0114] In addition, if Figure 7 and Figure 8 As shown, for the negative electrode 116, in the sample S33 not containing the ionic liquid 226, the discharge capacity is less than 100 μAh, so it is judged as unqualified (×). It is believed that since the sample S33 does not contain the ionic liquid 226, the contact between the particles of the oxide-based lithium ion conductive solid electrolyte 206 becomes a point contact, and the resistance between the particles becomes high, resulting in a decrease in the lithium ion conductivity in the electrode and at the interface between the electrode and other components, and a decrease in the capacity of the battery.

[0115] In contrast, in samples S21 to S32 (excluding sample S26) containing the ionic liquid 226, the discharge capacity was 100 μAh or more, and thus they were judged as acceptable (○) or excellent (◎). It is believed that since these samples contain the ionic liquid 226, the ionic liquid 226 that functions as a lithium ion conduction path is interspersed between particles of the oxide-based lithium ion conductive solid electrolyte 206, and the lithium ion conductivity at the grain boundary is improved. As a result, the lithium ion conductivity in the electrode and at the interface between the electrode and other components is improved, and the battery capacity is improved. From this result, it can be said that when the negative electrode 116 contains the ionic liquid 226 in addition to the oxide-based lithium ion conductive solid electrolyte 206 and the negative electrode active material 216, the lithium ion conductivity in the electrode and at the interface between the electrode and other components can be improved.

[0116] It should be noted that in samples S27 to S32, since the discharge capacity is more than 400 μAh, it is judged to be excellent (◎). In these samples, the volume content of the negative electrode active material 216 is more than 40 volume % and less than 85 volume %, the volume content of the oxide-based lithium ion conductive solid electrolyte 206 is more than 5 volume % and less than 40 volume %, and the volume content of the ionic liquid 226 is more than 3 volume % and less than 35 volume %. On the other hand, sample S26 has ionic liquid seepage during molding, so it is judged to be unmeasurable (-). From these results, it can be said that if the electrode meets the above-mentioned conditions on the volume content, it can effectively improve the lithium ion conductivity in the electrode and at the interface between the electrode and other components while suppressing the occurrence of ionic liquid seepage.

[0117] A-7. Preferred embodiment of LLZ type ion conductive powder:

[0118] As described above, the lithium ion conductor in the present embodiment contains LLZ-based ion conductive powder (ion conductive solid electrolyte powder having a garnet-type crystal structure containing at least Li, La, Zr, and O). As the LLZ-based ion conductive powder, it is preferable to use a material containing at least one element selected from the group consisting of Mg, Al, Si, Ca (calcium), Ti, V (vanadium), Ga (gallium), Sr, Y (yttrium), Nb (niobium), Sn (tin), Sb (antimony), Ba (barium), Hf (hafnium), Ta (tantalum), W (tungsten), Bi (bismuth), and lanthanide elements. If such a composition is adopted, the LLZ-based ion conductive powder shows good lithium ion conductivity.

[0119] In addition, as the LLZ-type ion conductive powder, it is preferred to use a material containing at least one of Mg and element A (A is at least one element selected from the group consisting of Ca, Sr and Ba) and each element contained satisfies the following formulas (1) to (3) in terms of molar ratio. It should be noted that the buried amount of Mg and element A is relatively large and inexpensive, so if Mg and / or element A are used as the replacement element of the LLZ-type ion conductive powder, a stable supply of LLZ-type ion conductive powder can be expected and costs can be reduced.

[0120] (1) 1.33 ≤ Li / (La+A) ≤ 3

[0121] (2) 0≤Mg / (La+A)≤0.5

[0122] (3)0≤A / (La+A)≤0.67

[0123] Furthermore, as the LLZ-based ion conductive powder, it is more preferable to use a material containing both Mg and the element A, wherein the molar ratio of each element contained satisfies the following formulas (1′) to (3′).

[0124] (1')2.0≤Li / (La+A)≤2.5

[0125] (2')0.01≤Mg / (La+A)≤0.14

[0126] (3')0.04≤A / (La+A)≤0.17

[0127] To state the above in another way, it can be said that the LLZ-based ion conductive powder preferably satisfies any one of the following (a) to (c), more preferably satisfies (c), and even more preferably satisfies (d).

[0128] (a) Mg is contained, and the content of each element satisfies 1.33≤Li / La≤3 and 0≤Mg / La≤0.5 in terms of molar ratio.

[0129] (b) The element A is contained, and the content of each element, calculated by molar ratio, satisfies 1.33≤Li / (La+A)≤3 and 0≤A / (La+A)≤0.67.

[0130] (c) Containing Mg and element A, the content of each element, in terms of molar ratio, satisfies 1.33≤Li / (La+A)≤3, 0≤Mg / (La+A)≤0.5 and 0≤A / (La+A)≤0.67.

[0131] (d) Containing Mg and element A, the content of each element, calculated by molar ratio, satisfies 2.0≤Li / (La+A)≤2.5, 0.01≤Mg / (La+A)≤0.14, and 0.04≤A / (La+A)≤0.17.

[0132] When the LLZ-type ion conductive powder satisfies the above (a), that is, when Li, La, Zr and Mg are contained in a manner satisfying the above formulas (1) and (2) in molar ratio, good lithium ion conductivity is exhibited. Although the mechanism is unclear, it is believed that, for example, when the LLZ-type ion conductive powder contains Mg, since the ionic radius of Li is close to the ionic radius of Mg, Mg is easily configured at the Li site where Li is configured in the LLZ crystal phase, and by replacing Li with Mg, vacancies are generated at the Li site in the crystal structure due to the difference in charge between Li and Mg, and Li ions become easy to move, resulting in improved lithium ion conductivity. In the LLZ-type ion conductive powder, when the molar ratio of Li to the sum of La and element A is less than 1.33 or greater than 3, not only is it easy to form an ion conductive powder having a garnet-type crystal structure, but it is also easy to form other metal oxides. The greater the content of other metal oxides, the smaller the content of the ion conductive powder having a garnet-type crystal structure is relatively, and the lithium ion conductivity of other metal oxides is low, so the lithium ion conductivity is reduced. The more Mg content in the LLZ-based ion conductive powder, the more Mg is arranged at the Li site, and vacancies are generated at the Li site, which improves the lithium ion conductivity. However, when the molar ratio of Mg to the sum of La and element A is greater than 0.5, other metal oxides containing Mg are easily formed. The greater the content of the other metal oxide containing Mg, the smaller the content of the ion conductive powder having a garnet-type crystal structure. Since the lithium ion conductivity of other metal oxides containing Mg is low, when the molar ratio of Mg to the sum of La and element A is greater than 0.5, the lithium ion conductivity decreases.

[0133] When the LLZ-type ion conductive powder satisfies the above (b), that is, when Li, La, Zr and element A are contained in a molar ratio to satisfy the above formulas (1) and (3), good lithium ion conductivity is shown. Although the mechanism is unclear, it is believed that, for example, when the LLZ-type ion conductive powder contains element A, since the ionic radius of La is close to the ionic radius of element A, element A is easily configured at the La site where La is configured in the LLZ crystal phase, and La is replaced by element A, lattice distortion occurs, and since La and element A have different charges, free Li ions increase, and lithium ion conductivity is improved. In the LLZ-type ion conductive powder, when the molar ratio of Li to the sum of La and element A is less than 1.33 or greater than 3, not only ion conductive powder having a garnet-type crystal structure is easily formed, but also other metal oxides are easily formed. The larger the content of other metal oxides, the smaller the content of ion conductive powder having a garnet-type crystal structure is relatively, and the lithium ion conductivity of other metal oxides is low, so the lithium ion conductivity is reduced. The more the content of element A in the LLZ-based ion conductive powder is, the more element A is arranged at the La site, the greater the lattice distortion is, and due to the difference in charge between La and element A, the free Li ions increase, and the lithium ion conductivity is improved. However, when the molar ratio of element A to the sum of La and element A is greater than 0.67, other metal oxides containing element A are easily formed. As the content of the other metal oxide containing element A increases, the content of the ion conductive powder having a garnet-type crystal structure relatively decreases, and the lithium ion conductivity of the other metal oxide containing element A is low, so the lithium ion conductivity decreases.

[0134] The above-mentioned element A is at least one element selected from the group consisting of Ca, Sr and Ba. Ca, Sr and Ba are Group 2 elements in the periodic table, easily become divalent cations, and have the common property of having similar ionic radii. The ionic radii of Ca, Sr and Ba are all close to La, so they are easy to replace La configured at the La site in the LLZ-type ion conductive powder. From the perspective of being able to be easily formed by sintering and being able to obtain high lithium ion conductivity, it is preferred that the LLZ-type ion conductive powder contains Sr among these elements A.

[0135] When the LLZ-type ion conductive powder satisfies the above (c), that is, when it contains Li, La, Zr, Mg and element A in a molar ratio that satisfies the above formulas (1) to (3), it can be easily formed by sintering, and the lithium ion conductivity is further improved. In addition, when the LLZ-type ion conductive powder satisfies the above (d), that is, when it contains Li, La, Zr, Mg and element A in a molar ratio that satisfies the above formulas (1') to (3'), the lithium ion conductivity is further improved. Although the mechanism is unclear, it is believed that, for example, by replacing Li at the Li site in the LLZ-type ion conductive powder with Mg and replacing La at the La site with element A, vacancies are generated at the Li site and the free Li ions increase, and the lithium ion conductivity becomes better. In addition, from the perspective of being able to obtain a high lithium ion conductivity and a lithium ion conductor with a high relative density, the LLZ-based ion conductive powder preferably contains Li, La, Zr, Mg and Sr in a manner satisfying the above formulas (1) to (3), particularly in a manner satisfying the above formulas (1') to (3').

[0136] In any of the above (a) to (d), the LLZ-based ion conductive powder preferably contains Zr in a molar ratio to satisfy the following formula (4). By containing Zr within this range, an ion conductive powder having a garnet type crystal structure can be easily obtained.

[0137] (4) 0.33 ≤ Zr / (La+A) ≤ 1

[0138] B. Modifications:

[0139] The technology disclosed in this specification is not limited to the above-described embodiment, and can be modified in various forms without departing from the gist thereof. For example, the following modifications are also possible.

[0140] The structure of the all-solid-state battery 102 in the above embodiment is only an example, and various changes can be made. For example, in the above embodiment, the positive electrode 114 and the negative electrode 116 contain an oxide-based lithium ion conductive solid electrolyte, an active material, and an ionic liquid, but the positive electrode 114 and the negative electrode 116 may contain other components in addition to these components.

[0141] In the above embodiment, a structure containing an oxide-based lithium ion conductive solid electrolyte, an active material, and an ionic liquid is used for both the positive electrode 114 and the negative electrode 116, but this structure may be used for only one of the positive electrode 114 and the negative electrode 116. For example, a structure in which the positive electrode 114 contains an ionic liquid but the negative electrode 116 does not contain an ionic liquid may be used.

[0142] In addition, in the above embodiment, the materials forming each element constituting the all-solid battery 102 are merely examples, and each element may be formed by other materials. In addition, in the above embodiment, the manufacturing method of the all-solid battery 102 is merely an example, and other manufacturing methods may be used.

[0143] In addition, the technology disclosed in this specification is not limited to electrodes for all-solid-state batteries 102, but can also be applied to electrodes for other power storage devices (for example, lithium-air batteries, lithium-liquid flow batteries, solid capacitors, etc.).

[0144] Explanation of symbols

[0145] 102 : All-solid lithium ion secondary battery 110 : Battery body 112 : Solid electrolyte layer 114 : Positive electrode 116 : Negative electrode 154 : Positive electrode side current collector 156 : Negative electrode side current collector 204 , 206 : Oxide-based lithium ion conductive solid electrolyte 214 : Positive electrode active material 216 : Negative electrode active material 224 , 226 : Ionic liquid 300 : Pressing jig.

Claims

1. An electrode for an electric storage device, characterized in that: contain: Oxide-based lithium-ion conductive solid electrolytes, Active materials, and Ionic liquids, The active material is LiFePO4, Li(Co 1 / 3 Ni 1 / 3 Mn 1 / 3 )O2 or LiNi 0.8 Co 0.15 Al 0.05 Any one in O2, The total volume of each component constituting the electrode for the power storage device is 100 volume%, The volume content of the active material is 44.1 volume % or more and 76.0 volume % or less, The volume content of the oxide-based lithium ion conductive solid electrolyte is 5 volume % or more and 30 volume % or less, and The volume content of the ionic liquid is 9 volume % or more and 18 volume % or less.

2. The electrode for a power storage device according to claim 1, wherein The oxide-based lithium ion conductive solid electrolyte has a garnet-type crystal structure containing at least Li, La, Zr, and O.

3. The electrode for a power storage device according to claim 1, wherein The oxide-based lithium ion conductive solid electrolyte is Li7La3Zr2O 12 The active material is LiNi 0.8 Co 0.15 Al 0.05 O2, the ionic liquid is 1-ethyl-3-methylimidazole dissolved with 1.0 mol / L lithium bis(fluorosulfonyl)imide Bis(fluorosulfonyl)imide.

4. A power storage device comprising a solid electrolyte layer, a positive electrode, a negative electrode and a current collector, characterized in that: At least one of the positive electrode and the negative electrode is the electrode for a power storage device according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • High conducting oxide - sulfide composite lithium superionic conductor

    US20150171463A1

  • Battery

    CN107394254A

  • Solid electrolyte composition, binder particle, all-solid secondary battery sheet, all-solid secondary battery electrode sheet and all-solid secondary battery, and production method therefor

    CN108370061A

  • Positive electrode mixture composition

    JP2013191547A

  • Composite Electrode with Ionic Liquid for All-Solid-State Battery, Method Of Manufacturing The Same, And All-Solid-State Lithium Battery Comprising The Same

    KR101953738B1